MENUMBUHKAN KEMANDIRIAN SISWA SELAMA PEMBELAJARAN DARING SEBAGAI DAMPAK COVID-19 DI SD - Rida Fironika Kusumadewi; Sari Yustiana; Khoirotun Nasihah (Jurnal Riset Pendidikan Dasar (JRPD), 2020)
Abstract. Currently, almost countries around the world have contracted Corono Virus Disease (Covid-19). This Virus initially appeared in China, precisely in Wuhan City at the end of 2019. This Virus is very dangerous because of its transmission from humans to other people so fast that even now there is no drug or vaccine that can overcome the corona virus. Indonesia is no exception, which is increasingly increasing the number of COVID-19 cases. The existence of this plague certainly has a big impact in almost all aspects of economic, social, cultural, even education. Almost all levels of education that were originally carried out in schools are now switching online/online. This article aims to explain  how the influence of independent character education on students during online learning. This study was conducted through literature study looking at the resulr of surveys ad journals from electronic media. The conclusion of this article is the inculcation of independent character during online learning in elementary school.